A Novel Digital Signature Scheme for Application of Document Review in a Linearly Hierarchical Organization - Iuon-Chang Lin; Chin-Chen Chang (IIH-MSP 2008 : 2008 Fourth International Conference on Intelligent Information Hiding and Multimedia Signal Processing : 15-17 August 2008, Harbin, China, 2008)
In practical applications, an official document may be involved in several subjects or departments, and it usually needs to be reviewed by different levels of participant managers in a linearly hierarchical organization. Each reviewer would give some comments for those documents and sends them to the next reviewer for the further review. In an organization, the order of reviewers depends on the hierarchical position and the function of office. Each participant reviewer needs to sign on those documents they have reviewed as a proof of confirmation. In this paper, we are going to propose a novel digital signature scheme for applying to the above case. Our scheme provides a function for the reviewers to examine the documents which have been reviewed by those previous reviewers, and each of previous comments would still be kept integrity. The sequence of reviewal also could be verified by using the generated signatures. The other important property of our proposed scheme is that the reviewing results are able to be recovered by the received digital signatures with some public keys. Thus, this scheme greatly benefits the organizations by not only the convenience of paper work process but also the reduction of overheads in storage and communications.